Ong Keng Yong [Singapore, Ministry of Foreign Affairs, Civil Service] - Ong, Keng Yong (Institutional Knowledge at Singapore Management University, 2016)
Ong Keng Yong, a law graduate who worked in MFA (Ministry of Foreign Affairs) specialising in Middle East, recalls his initial years working under S. Rajaratnam, and SR Nathan. Having served as the Secretary General of ASEAN, he shares with DNA the strategic contributions of ASEAN (Association of Southeast Asian Nations) and AEC (ASEAN Economic Community) to Singapore, highlighting the uniqueness of ASEAN socialisation at the leadership level.